Manajemen Kyai dalam Perencanaan Pendidikan di Pondok Pesantren Nurul Huda Al Karimi Mereng Warungpring Pemalang - Imam Subarkah; Muhdir Muhdir; Luthfil Khakim; Imam Satibi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
This study aims to determine the functions of educational planning at the Pondok Nurul Huda Al Karimi. In this study, the data was obtained through observation, documentation, and interviews. Subjects and informants in this study were extracted from informants who have key roles in managing or implementing manage decision-makers in the educational process, namely boarding school caregivers, madrasa heads, ustadz, and administrators of the Nurul Huda Al Karimi Islamic Boarding School by using purposive sampling and snowball sampling. The main issues discussed in this study reveal how education management is seen from the educational planning function of the Nurul Huda Al Karimi Islamic boarding school, The results of this study reveal that there is a planning function for educational development carried out at the Nurul Huda Al Karimi Islamic Boarding School in Mereng Warungpring Pemalang, and that the curriculum planning is quite good. Furthermore, in planning for human resources or educators, they have met academic quality standards. Educational planning for the Nurul Huda Al Karimi Islamic boarding school by KH. Machmud, The organizational structure of the Nurul Huda Al Karimi Islamic boarding school is led by KH. Khotibul Umam, Education Direction by the curriculum section, and its control by caregivers.